2022
DOI: 10.1038/s41598-021-04509-9
|View full text |Cite
|
Sign up to set email alerts
|

A 6-mRNA host response classifier in whole blood predicts outcomes in COVID-19 and other acute viral infections

Abstract: Predicting the severity of COVID-19 remains an unmet medical need. Our objective was to develop a blood-based host-gene-expression classifier for the severity of viral infections and validate it in independent data, including COVID-19. We developed a logistic regression-based classifier for the severity of viral infections and validated it in multiple viral infection settings including COVID-19. We used training data (N = 705) from 21 retrospective transcriptomic clinical studies of influenza and other viral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Transcriptomic approaches have shown that they could discriminate between distinct physio-pathological states of the COVID-19 (e.g paucisymptomatic, mild/moderate and severe) ( 22 ). Recently, a 6-gene signature was identified to predict COVID-19 mortality based on cohort explorative approaches ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomic approaches have shown that they could discriminate between distinct physio-pathological states of the COVID-19 (e.g paucisymptomatic, mild/moderate and severe) ( 22 ). Recently, a 6-gene signature was identified to predict COVID-19 mortality based on cohort explorative approaches ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we propose the use of a tool that captures the immune profile of a patient directly through processing blood samples without added laborious hands-on time and resource. In regard, none of the elegant transcriptomic-based machine learning models which were previously described to predict mortality in COVID-19 ( 21 , 23 ) can be easily implemented at the patient´s bedside due to constraints with RNAs processing and standardization of the measures. Similarly, while demographic parameters such as age or clinical parameters such as the SOFA score can readily be obtained at patient admission, some other variables used to build models in the literature are not so easily accessed.…”
Section: Discussionmentioning
confidence: 99%
“…The deep neural network (DNN) model earned the highest accuracy values in all three datasets. Buturovic et al [46] sought to build a blood-based host gene expression classifier for the severity of viral infections, including COVID-19. They created a logistic regression-based classifier for viral infection severity and validated it in a variety of viral infection situations, including COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the hub genes may represent candidate biomarkers for diagnosis as well as be targeted in the therapeutic procedure. For example, DEFA4 was one of 6 genes constructed as a classifier that can predict the severity of different viral infections including the SARS-CoV 2 virus (COVID-19) [ 40 ]. All studies are summarized in Figure 2 .…”
Section: Human Defensin Alpha 4 ( Defa4 )mentioning
confidence: 99%